Leukodepleted Packed Red Blood Cells Transfusion in Patients Undergoing Major Cardiovascular Surgical Procedure: Systematic Review and Meta-Analysis - Daniel Simancas-Racines; Ingrid Arevalo-Rodriguez; Gerard Urrutia; Diana Buitrago-Garcia; Solange Núñez-González; María José Martínez-Zapata; Eva Madrid; Xavier Bonfill; Ricardo Hidalgo-Ottolenghi (Cardiology Research and Practice, 2019)
Background. Leukocytes contained in the allogeneic packed red blood cell (PRBC) are the cause of certain adverse reactions associated with blood transfusion. Leukoreduction consists of eliminating leukocytes in all blood products below the established safety levels for any patient type. In this systematic review, we appraise the clinical effectiveness of allogeneic leukodepleted (LD) PRBC transfusion for preventing infections and death in patients undergoing major cardiovascular surgical procedures. Methods. We searched randomized controlled trials (RCT), enrolling patients undergoing a major cardiovascular surgical procedure and transfused with LD-PRBC. Data were extracted, and risk of bias was assessed according to Cochrane guidelines. In addition, trial sequential analysis (TSA) was used to assess the need of conducting additional trials. Quality of the evidence was assessed using the GRADE approach. Results. Seven studies met the eligibility criteria. Quality of the evidence was rated as moderate for both outcomes. The risk ratio for death from any cause comparing the LD-PRBC versus non-LD-PRBC group was 0.69 (CI 95% = 0.53 to 0.90; I2 = 0%). The risk ratio for infection in the same comparison groups was 0.77 (CI 95% = 0.66 to 0.91; I2 = 0%). TSA showed a conclusive result in this outcome. Conclusions. We found evidence that supports the routine use of leukodepletion in patients undergoing a major cardiovascular surgical procedure requiring PRBC transfusion to prevent death and infection. In the case of infection, the evidence should be considered sufficient and conclusive and hence indicated that further trials would not be required.